An example study on re-evaluation of historical earthquakes: 1789 Palu (Elazig) earthquake, Eastern Anatolia, Turkey - Kokum, Mehmet; Ozcelik, Fatih (Maden Tetkik ve Arama Genel Mudurlugu-Mta, 2020)
The East Anatolian Fault (EAF) is an active left-lateral strike-slip fault extending between Karliova (Bingol) in the northeast and Iskenderun Bay in the southwest. The Palu, which is the subject of the study area, is located on the Palu segment of the EAF. The Palu segment starts from the northeast of Palu, and is approximately 77 km long, and reaches the Lake Hazar after passing the Baltasi Plain. Maximum shaking intensity in the earthquake listed in historical catalogs is estimated to have been Mercalli Intensity VIII, with conflicting accounts of as few as 8.000-10.000 to as many as 50.000 people killed. An examination of contemporary documents, books and administrative archives in the State Archives Head of Presidency Republic of Turkey for the district reveal that the extent of damage and the number of fatalities in the earthquake have been considerably inflated by these historical catalogs.